The multivariate social scientist : introductory statistics using generalized linear models - Hutcheson, Graeme D.; Sofroniou, Nick (SAGE, 1999)
Starting from simple hypothesis testing and then moving towards model-building, this book takes readers through the basics of multivariate analysis including: which tests to use on which data; how to run analyses in SPSS for Windows and GLIM4; how to interpret results; and how to report and present the reports.